Natural course of pain and disability following primary lumbar discectomy: protocol for a systematic review and meta-analysis. Issue 2 (23rd February 2016) - Rushton, A; Heneghan, N; Heijmans, M W; Staal, J B; Goodwin, P
Abstract : Introduction: Knowledge about the natural clinical course is needed to improve understanding of recovery postsurgery as outcome is poor for some patients. Knowledge of the natural clinical course of symptoms and disability will inform optimal timing and the nature of rehabilitation intervention. The objective of this study is to provide first evidence synthesis investigating the natural clinical course of disability and pain in patients aged >16 years post primary lumbar discectomy. Methods and analysis: A systematic review and data synthesis will be conducted. Prospective cohorts that include a well-defined inception cohort (point of surgery) of adult participants who have undergone primary lumbar discectomy/microdiscectomy will be included. Outcomes will include measurements reported on 1 or more outcomes of disability and pain, with a baseline presurgery measurement. Following development of the search strategy, 2 reviewers will independently search information sources, assess identified studies for inclusion, extract data and assess risk of bias. A third reviewer will mediate on any disagreement at each stage. The search will employ sensitive topic-based strategies designed for each database from inception to 31 January 2016. There will be no language or geographical restrictions. Risk of bias will be assessed using a modified QUality In Prognostic Studies (QUIPS) tool . Data will be extracted for time points where follow-up was at least 80%. Means and 95% CIs will be plotted over time for pain and disability. All results will be reported in the context of study quality. Ethics and dissemination: This review will provide the first rigorous summary of the course of pain and disability across all published prospective cohorts. The findings will inform our understanding of when to offer and how to optimise rehabilitation following surgery. Results will be published in an open access journal. The study raises no ethical issues. PROSPERO registration number: CRD42015020806.